(untitled) (Periphērica, 2020)
This article analyzes the ambiguity in the film La guerre est finie ([The War Is Over] 1966, director Alain Resnais, screenwriter Jorge Semprún) whose declarative title becomes a question in the title of the permanent exhibit at the Reina Sofía National Museum in Madrid: Is the War Over? Art in a Divided World (1945-1968). The works invite the viewer to question the nationalism that catapulted the Spanish Civil War, whose victory marked the first triumph for European fascisms and concomitant genocides. While the film entirely lacks symbols of irrefutable national identity, the paintings incorporate and subvert certain icons of (regional, Francoist, Nazi or Fascist) nationalism, as well as emblems of the Spanish Republic and Spain. The artworks respond in theme and form to nationalist ideology and esthetics. Although the film whose screenwriter Jorge Semprún had been imprisoned in the Nazi camp at Buchenwald—limits itself to implicit allusions to the eradication of the domestic enemy on Iberian soil and the so-called stateless undesirables exiled in foreign lands, the exhibit explicitly references Nazism and other 20th-century genocides. The collection of works exemplifies Aharon Appelfeld’s assertion: that only art has the ability to redeem suffering from the abyss. The film and the plastic works respond not only to nationalist ideologies and concomitant lived and witnessed experiences, but also to nationalist art. Through the visual counternarratives that give voice to myriad victimizations, these works make manifest and denounce, in theme and form, the anti-intellectualization and the fervent sentiment of political zeal.